Konstitusionalitas Putusan Mahkamah Konstitusi Dalam Perubahan Desain Demokrasi Elektoral Pasca Pemilu Serentak Di Indonesia - Dairani Dairani; Mustajib Mustajib (Universitas Moch. Sroedji, 2026)
This study aims to analyze the position of Constitutional Court decisions in shaping the design of electoral democracy in Indonesia following the implementation of the simultaneous election system. Recent constitutional developments have demonstrated the increasing influence of Constitutional Court decisions on the regulation of the electoral system, ranging from candidacy thresholds and electoral mechanisms to the administration of general elections and regional head elections. This phenomenon has generated debates regarding the limits of the Constitutional Court's authority as the guardian of the Constitution and the potential shift of its role from a negative legislator to a positive legislator. This research employs a normative legal research method using statutory, conceptual, and case approaches. The primary legal materials consist of the 1945 Constitution of the Republic of Indonesia, election-related legislation, and Constitutional Court decisions concerning the design of electoral democracy. The analysis is conducted prescriptively to assess the conformity of Constitutional Court decisions with the principles of constitutional democracy and popular sovereignty. The findings reveal that Constitutional Court decisions occupy a strategic position in shaping the direction of Indonesia’s electoral democracy through progressive constitutional interpretation. However, several decisions indicate a tendency toward judicial activism, which has implications for the expansion of the Constitutional Court’s role in the creation of legal norms. Therefore, clear parameters regarding the limits of constitutional judges’ authority are necessary to maintain a balance between constitutional protection, democracy, and the principle of separation of powers within Indonesia’s constitutional system.